Intensity of Use Gadget Against Learning Achievement Among Children In Elementary School Students - Ridhoni Adriyanto; Dra. Taufik Suprihartini, M.Si (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
The development of technology is currently experiencing rapid growth. This can be evidenced by the many innovations - innovations that have been made in this world. One example is the simplest form that gadget. Habits of children who use the gadget has an influence on the brain's ability to capture information. One of them is when they are at school and get a lesson given by the teacher. Due to the influence of the habit of using the gadgets of children - child trouble when understanding what is conveyed by the teacher. This study aims to determine the relationship of the intensity of the use of the gadget on the learning achievement of children. In addition to explaining the conditions of use of gadgets among elementary school students. The rationale used is the theory Media Equation by Byron Reeves and Clifford Nass (1996). This type of research is quantitative descriptive. That is the kind of research that is intended to create a picture of systematic, factual and accurate about the facts and the properties of certain populations. The population used are elementary school students who attend school in SDN Gayamsari 02. Sampling in this study using total sampling technique. samples used are students - who attend class V SDN Gayamsari 02 totaling 71 people. Analysis of the data used is the t test with SPSS 20. The t-test is basically indicates how far the influence of independent variables on the dependent variable. Hypothesis test results showed t value of 1.367 with sig 0.176 or greater than 0.05. It shows that there is a negative correlation between the intensity of use of gadgets on the learning achievement of children. This proves our hypotheses rejected. The conclusion was that the use of the gadget does not affect the learning achievement of children. Due to the use of the gadget is not one of the factors that cause the learning achievement of children is lowered. Factors affecting the learning achievement of children is the factor that comes from within and outside the child's environment. This was reinforced by the R-square value of 2.6% which implies that the effect of variable intensity of the use of the gadget as an independent variable is 2.6% so as not to affect the learning achievement as the dependent variable.